Estudio de demanda y empleabilidad para determinar la pertinencia de un programa de Maestría en Marketing y Comercio internacional en la Universidad de Otavalo. - Hualpa, Lizeth C. (2022)
The objective of this research work was to analyze and structure, strategically, the creation and execution of a master's degree program that contains and maintains the viable conditions of study, directed to the areas related to marketing and international trade, programmed for students, in a national form and, specifically, to the northern zone of the country. For this purpose, the study was carried out in public and private institutions, as well as with graduate students in areas related to the management of marketing and international trade of the institutions. This allowed us to receive ideas, suggestions and evaluations in order to implement a curriculum according to the needs of the institutions and civil society. Comprehensive educational training at the higher level and directly at the fourth level should be developed based on the employability of theory and practice, learned in the classroom, as well as on the experience of companies and professionals, considering that they need fundamental tools to carry out effective financial management. With this preamble, the offer of the present program of studies is maintained with positive viability in all aspects. From this point of view, the University of Otavalo must generate the necessary and sufficient conditions, so that there is a sustained and reliable relevance and the Master's program in Marketing and International Trade can be applied.